Consumer benefits from increased competition in shopping outlets: Measuring the effect of Wal-Mart - Jerry A. Hausman; Ephraim Leibtag (Centre for Microdata Methods and Practice (cemmap), 2006)
Consumers often benefit from increased competition in differentiated product settings. In previous research Hausman (1997a, 1997b, 1999, 2002) has estimated the increased consumer welfare from the introduction of new brand, e.g. Apple Cinnamon Cheerios, and new products, e.g. mobile telephones. In this paper we consider consumer benefits from increased competition in a differentiated product setting: the spread of nontraditional retail outlets. Non-traditional outlets, including supercenters, warehouse club stores, and mass merchandisers have grown in popularity and nearly doubled their share of consumer food-at-home expenditures from 1998 to 20033. Within this non-traditional retail group, supercenters have experienced the largest increase over this time period, but warehouse club stores and dollar stores have also experienced significant increases in their share of the consumer food dollar as U.S. consumers attempt to find the best combination of prices and services at their retailer of choice.
Keywords: 330; Wettbewerb; Einzelhandel; SB-Center; Wohlfahrtsanalyse; USA